Anteseden Brand Loyalty : Studi Empiris pada Pelanggan Tolak Angin Herbal di DKI Jakarta - Grachella Chrisencia; Vita Briliana (Jurnal Bisnis dan Akuntansi, 2022)
The purpose of this study is to analyze and examine the influence of brand satisfaction, brand image, brand impact, and brand value toward brand loyalty on Tolak Angin Herbal customers in DKI Jakarta. The research form used in this study is descriptive and causal research, using five points of likert scale to measure all variables. Sample collected using purposive sampling technique with primary and secondary data and using 129 respondents. Data analytic method using in this study is multiple linear regression. The result of this research has shown that brand satisfaction, brand image, brand impact and brand value have an effect on brand loyalty to Tolak Angin Herbal customers in DKI Jakarta.